2021
DOI: 10.3390/agronomy11030513
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Heterogeneity in Accessions of a Winter Barley Core Collection Assessed on Postulated Specific Powdery Mildew Resistance Genes

Abstract: Gene bank accessions are necessary for implementing many research and breeding projects. However, a great number of accessions are contaminated or confused. If such accessions are used, the results obtained from these projects are inaccurate and non-reproducible. There are methods that allow almost perfect genotype identification; nevertheless, they are relatively recent and results cannot be compared with the characteristics of the original accessions. Growing resistant cultivars is an environmentally safe an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…This contribution describes the identification of the powdery mildew resistance genes in single-plant progenies (SPPs) of accessions of the core collection (CC) of the Czech winter barley gene bank. Results from a similar project have already been reported [ 8 ], but more than 85% of the accessions showed heterogeneity in their resistance and identification of resistances was limited. Therefore, the aims of this study were i) to grow a technically-manageable group of homogeneous samples (lines) in order to record the most frequent genotypes present in each accession; ii) to identify resistance genes in each of them, and iii) to evaluate their authenticity.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…This contribution describes the identification of the powdery mildew resistance genes in single-plant progenies (SPPs) of accessions of the core collection (CC) of the Czech winter barley gene bank. Results from a similar project have already been reported [ 8 ], but more than 85% of the accessions showed heterogeneity in their resistance and identification of resistances was limited. Therefore, the aims of this study were i) to grow a technically-manageable group of homogeneous samples (lines) in order to record the most frequent genotypes present in each accession; ii) to identify resistance genes in each of them, and iii) to evaluate their authenticity.…”
Section: Introductionmentioning
confidence: 76%
“…The first cultivar with a gene located at the Mla locus was Vogelsanger Gold ( Mla6 ) derived from wild barley ( Hordeum vulgare subsp. spontaneum ) and many subsequent cultivars were bred with other new resistances, mainly alleles of Mla locus [ 6 , 8 ]. Later, it was found that even European landraces carry some specific resistance genes completely ineffective in the field [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gene bank accessions are commonly characterized by high genotypic heterogeneity [ 11 ]. Therefore, ear progenies of the tested cultivars were grown for this project.…”
Section: Discussionmentioning
confidence: 99%
“…The following methods, especially in Section 2.2 and Section 2.3 , are similar to those previously described [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, Reinstädler et al [ 48 ] reported that one of eight “ mlo -11 mutant alleles” tested was not mlo -11. Recently, it was also reported that about 85% of accessions of the core collection of the Czech winter barley gene bank was heterogenous [ 49 ]. In addition, we found that the wild-type Diamant seeds were suspected to be heterogenous due to contamination with other mlo mutant alleles, and avoided using them.…”
Section: Discussionmentioning
confidence: 99%